Analisis Performa Sistem Monitoring IoT Pada Pengujian Switch Cycle Lampu LED - Dimas Tri Herfiantoro; Vicky Prasetia; Hera Susanti; Muhamad Yusuf; Sugeng Dwi Riyanto; Arif Ainur Rafiq (P3M Politeknik Negeri Cilacap, 2026)
Lamps have a limited lifetime and may experience performance degradation due to repeated on–off operations (switch cycles). However, most developed testing devices are still focused on recording the number of cycles without integrating real-time monitoring of electrical and temperature parameters within a single Internet of Things (IoT)-based system. This research aims to design and develop an IoT-based lamp switch cycle testing device connected to an Android application through the Blynk platform. The developed system uses an LDR sensor for light detection, a PZEM-004T sensor for measuring voltage, current, and power, and an MLX90614 sensor for temperature monitoring. The ESP32 microcontroller acts as the main control and data communication unit. The tested parameters include switching cycles, temperature, voltage, current, and power, which can be monitored in real-time through an LCD and the Blynk application. The test results show that the 5 W LED lamp achieved 192,395 cycles with an average temperature of 37.5°C, voltage of 221.5 V, current of 0.018 A, and power of 4.03 W. The 9 W TL LED lamp reached 226,039 cycles with a temperature of 31°C, voltage of 221.7 V, current of 0.031 A, and power of 6.64 W. The system is equipped with electrical protection features and an automatic reset mechanism, enabling safe and continuous testing. This research provides an integrated system for evaluating lamp durability and performance characteristics through real-time monitoring of switch cycles, electrical parameters, and temperature.